PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE GI UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 002 SINTONG KECAMATAN TANAH PUTIH - Masturah '; Hendri Marhadi Hendri Marhadi; Erlisnawati ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract The problem this reaserch student achievement fourth graderes yields social studies class SDN 002 Sintong average 50.4 As a minimum completeness criteria value ( KKM ) IPS is among 70 students totaling 22 people only 10 people who reached the KKM with classical completeness 45.45 % . This research is Classroom Action Research ( CAR) conducted aimed at improving student learning outcomes IPS Elementary School fourth grade 002 Sintong academic year 2013/2014 with the use of cooperative learning model GI type was conducted on March 26, 2014 until 23 April 2014 . Subjects is the fourth graders were 22 students consisting of 12 male students and 10 female students . Parameters measured were the result of student learning , mastery learning , student learning activities and teacher activities . Teacher activity during the learning process by using Cooperative Learning Implementation Model GI Type in the first cycle the first meeting 56.25 % with enough categories , the first cycle of the second meeting of 68.75 % with category Enough . Increased 12.5 % . In the second cycle the first meeting of 84.38 % with a very good category , meeting the second cycle II 90.63 % with very good category 6.25 % increase . Activities of students during the learning process by using the application of models of inquiry in the first cycle the first meeting of 50.00 % with enough categories , the first cycle of the second meeting of 56.25 % with category Enough . 6.25 % increase . In the second cycle the first meeting of 81.25 % with a very good category . In the second cycle the second meeting of 87.50 % with a very good category 6:25 % increase . Cooperative Learning Model Type Group Investigation in the process of learning can improve student learning outcomes IPS from baseline score ( 45.45 % ) to UH I ( 68.18 % ) with increased 22.73 % , the base score ( 45.45 % ) to UH II ( 81.81 % ) increased by 36.36 % . Research in Public Elementary School fourth grade 002 Sintong prove that the implementation of cooperative learning model to improve learning outcomes GI IPS grade IV Elementary School 002 Sintong White Land District of Rokan Hilir . Key Word : Model Learning GI, fourth graderes Students Achievement.